LRRC8A is dispensable for a variety of microglial functions and response to acute stroke. Issue 6 (12th February 2022) - Cook, James R.; Gray, Anna L.; Lemarchand, Eloise; Schiessl, Ingo; Green, Jack P.; Newland, Mary C.; Dyer, Douglas P.; Brough, David; Lawrence, Catherine B.
Abstract: Microglia, resident brain immune cells, are critical in orchestrating responses to central nervous system (CNS) injury. Many microglial functions, such as phagocytosis, motility and chemotaxis, are suggested to rely on chloride channels, including the volume‐regulated anion channel (VRAC), but studies to date have relied on the use of pharmacological tools with limited specificity. VRAC has also been proposed as a drug target for acute CNS injury, and its role in microglial function is of considerable interest for developing CNS therapeutics. This study aimed to definitively confirm the contribution of VRAC in microglia function by using conditional LRRC8A‐knockout mice, which lacked the essential VRAC subunit LRRC8A in microglia. We demonstrated that while VRAC contributed to cell volume regulation, it had no effect on phagocytic activity, cell migration or P2YR12‐dependent chemotaxis. Moreover, loss of microglial VRAC did not affect microglial morphology or the extent of ischemic damage following stroke. We conclude that VRAC does not critically regulate microglial responses to brain injury and could be targetable in other CNS cell types (e.g., astrocytes) without impeding microglial function. Our results also demonstrate a role for VRAC in cell volume regulation but show that VRAC is not involved in several major cellular functions that it was previously thought to regulate, and point to other, alternative mechanisms of chloride transport in innate immunity. Main Points: LRRC8A KO does not affect microglial phagocytosis or migration. LRRC8A does not regulate microglial P2RY12‐dependent chemotaxis or morphology. Microglial LRRC8A does not affect ischaemic stroke damage.